Generation of Sesame Mutant Population by Mutagenesis and Identification of High Oleate Mutants by GC Analysis - Ming Li Wang; Brandon Tonnis; Xianran Li; John Bradly Morris (Plants, 2023)
Sesame is one of the important oilseed crops in the world. Natural genetic variation exists in the sesame germplasm collection. Mining and utilizing the genetic allele variation from the germplasm collection is an important approach for seed quality improvement. The sesame germplasm accession, PI 263470, which has a significantly higher level of oleic acid (54.0%) than the average (39.5%), was identified by screening the entire USDA germplasm collection. The seeds from this accession were planted in a greenhouse. Leaf tissues and seeds were harvested from individual plants. DNA sequencing of the coding region of the fatty acid desaturase gene (FAD2) confirmed that this accession contained a natural mutation of G425A which may correspond to the deduced amino acid substitution of R142H leading to the high level of oleic acid, but it was a mixed accession with three genotypes (G/G, G/A, and A/A at the position). The genotype with A/A was selected and self-crossed for three generations. The purified seeds were used for EMS-induced mutagenesis to further enhance the level of oleic acid. A total of 635 M2 plants were generated from mutagenesis. Some mutant plants had significant morphological changes including leafy flat stems and others. M3 seeds were used for fatty acid composition analysis by gas chromatography (GC). Several mutant lines were identified with high oleic acid (70%). Six M3 mutant lines plus one control line were advanced to M7 or M8 generations. Their high oleate traits from M7 or M8 seeds harvested from M6 or M7 plants were further confirmed. The level of oleic acid from one mutant line (M7 915-2) was over 75%. The coding region of FAD2 was sequenced from these six mutants, but no mutation was identified. Additional loci may contribute to the high level of oleic acid. The mutants identified in this study can be used as breeding materials for sesame improvement and as genetic materials for forward genetic studies.